Edukasi Penyuluhan Kesehatan Sosialisasi Cuci Tangan Pakai Sabun Pada Murid Sekolah Dasar Di Deli Serdang - Maria Haryanti; Ihsan Kurniawan; Veronica Damanik (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
One of the infectious diseases that affect nutritional status is helminthiasis. Chronic worms will cause a lack of carbohydrates, protein and blood loss which will indirectly reduce productivity. Worms in children will also lower their immune system so they are susceptible to other diseases. Worms in toddlers will inhibit their growth and development and even become a risk factor for failure to thrive. Community service activities are carried out at an elementary school located in Deli Serdang. This community service method is used in the form of posters and demonstrations and counseling, while posters are given to grade 2 elementary school students, and then students from the Helvetia nursing academy guide direct demonstrations to grade 2 students and then practice by grade 2 students. The elementary school until students know how to wash their hands, counseling was carried out by a team from the Helvetia Health Institute together with lecturers and students of the Nursing Academy study program in order to apply the knowledge and knowledge distributed to grade 2 elementary school students.